2015
DOI: 10.1021/acs.jafc.5b04398
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Constitutive and Induced Biosynthesis of Mono- and Sesquiterpenes in Grapes (Vitis vinifera): A Key to Unlocking the Biochemical Secrets of Unique Grape Aroma Profiles

Abstract: The present review integrates current knowledge on mono- and sesquiterpenes in grapes with a special focus on biochemical and physiological aspects. Recent research has impressively shown the prominence of terpenoid metabolism in grapevine (Vitis sp). The 69 putatively functional mono- and sesquiterpene synthases that were identified by the analysis of the updated 12-fold sequencing and assembly of the grapevine genome deliver the scaffolds for structural diversity and display a surprising expansion of the ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 103 publications
1
61
1
2
Order By: Relevance
“…All the terrestrial plant genera genomes examined to date appear to harbor diterpene synthase genes for kaurene biosynthesis, a precursor to gibberellins and gibberellin-like growth regulators. For mono-and sesquiterpene synthase genes, the angiosperms Arabidopsis and Vitis harbor 27 and 66 annotated genes, respectively (Chen et al, 2011;Vaughan et al, 2013;Schwab and Wüst, 2015). In the case of non-seed plants like Selaginella, 48 mono-and sesquiterpene synthase genes were predicted (Li et al, 2012), while Physcomitrella was found to contain only one functional diterpene synthase gene (Hayashi et al, 2006).…”
Section: Developmental Profile Of Terpenes In M Polymorphamentioning
confidence: 99%
“…All the terrestrial plant genera genomes examined to date appear to harbor diterpene synthase genes for kaurene biosynthesis, a precursor to gibberellins and gibberellin-like growth regulators. For mono-and sesquiterpene synthase genes, the angiosperms Arabidopsis and Vitis harbor 27 and 66 annotated genes, respectively (Chen et al, 2011;Vaughan et al, 2013;Schwab and Wüst, 2015). In the case of non-seed plants like Selaginella, 48 mono-and sesquiterpene synthase genes were predicted (Li et al, 2012), while Physcomitrella was found to contain only one functional diterpene synthase gene (Hayashi et al, 2006).…”
Section: Developmental Profile Of Terpenes In M Polymorphamentioning
confidence: 99%
“…Sesquiterpenes (C 15 ) are found in the berries' epicuticular wax. Within sesquiterpenes, the ketone rotundone is a key aroma compound for the peppery character of high‐quality Syrah wines …”
Section: Introductionmentioning
confidence: 99%
“…The enzymes and respective genes ( GAS, germacrene A synthase; GAO, germacrene A oxidase; COS, costunolide synthase ) were characterized in several Asteraceae species (Nguyen et al, 2010; Cankar et al, 2011; Ikezawa et al, 2011; Liu et al, 2011; Ramirez et al, 2013; Eljounaidi et al, 2014, 2015). Terpene synthase genes of the STL pathway have been identified in model plants (Kitaoka et al, 2015; Tholl, 2015) and crops, such as tomato (Falara et al, 2011) and grapevine (Schwab and Wust, 2015). However, to date, enzymes and genes leading to the Lc- and Lp-compounds have not been identified yet.…”
Section: Introductionmentioning
confidence: 99%